Avoiding blame when violating traffic rules: the development and validation of the justifications of traffic violations scale - Holman, Andrei C. (Psychology, crime & law, 2018)
Traffic norms violations are the most common form of law breaking. Our aim was to investigate a factor that might contribute to the massive disobedience to traffic laws, namely drivers’ use of self-legitimization strategies that allow them to transgress them without paying the psychological costs that would follow, such as regret or shame. Using the framework of the self-exoneration mechanisms described by the Social Cognitive Theory, we developed a measure assessing drivers’ strategies of justification of their traffic violations. Across two studies, we tested the psychometric proprieties of the Justifications of Traffic Violations scale (JTVs), its factorial structure, and its construct, external and incremental validity. Results showed that drivers self-exonerate when transgressing traffic laws predominantly through four strategies (Minimizing risks, Displacement of responsibility, Personal needs and Outcome - based justification) that are addressed by the JTVs and that construe one’s refraining from committing deviant driving behaviours as unnecessary, impossible or undesirable. The JTVs and each of its four specific cognitive mechanisms were found to be positively related to the most maladaptive driving styles, as well as to self-reported traffic offences and accidents, suggesting that these self-exonerating strategies favour the instilment and maintenance of habitual deviant behaviours on the road.